Intensitas Serangan Spodoptera frugiperda dari Fase Vegetatif dan Generatif Tanaman Jagung Sebagai Tanaman Inang - Muhammad Adi Pratama; Elila Anggaraini; Dika Trianisti; Sintia Dwi Putri; Yan Wenli Situmorang (xxxx-xxxx, 2020)
Pratama MA, Anggaraini E, Trianisti D, Putri SD, Situmorang YW. 2020. Attack intensity of spodoptera frugiperda from the vegetation and generative phases of corn as host plants. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang  20 Oktober 2020. pp. xx.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).An onslaught of corn plants (zea mays) can be one of the most important problems in corn production, the existence of a Fall armyworm in corn can cause damage and thus reduce economic value even more when the larvae invade the corn in both vegetative and generational growth phases. The purpose of an analysis of the intensity of the pest attack on each phase of corn growth which includes both the vegetation and the generative phase of the corn is one of the key factors in controlling the correct and appropriate conditions comparing the highest levels of the attack on corn. The material used in these observations is a plant that is stricken by the Fall armyworm in the vegetative and generic phases by methods of observation in the field. Based on literature studies, as one of the most strategic commodities, corn cultivation requires proper treatment at each phase of its growth in order to avoid pests. An analysis of the intensity of the pest attack on each phase of its growth can be a key factor in treating treatment as well as correct control over the pest attacks on the corn crop.